Qrator: A web-based curation tool for glycan structures - Eavenson, Matthew; Kochut, Krys J; Miller, John A; Ranzinger, René; Tiemeyer, Michael; Aoki, Kazuhiro; York, William S (Glycobiology (Oxford), 2015)
Most currently available glycan structure databases use their own proprietary structure representation schema and contain numerous annotation errors. These cause problems when glycan databases are used for the annotation or mining of data generated in the laboratory. Due to the complexity of glycan structures, curating these databases is often a tedious and labor-intensive process. However, rigorously validating glycan structures can be made easier with a curation workflow that incorporates a structure-matching algorithm that compares candidate glycans to a canonical tree that embodies structural features consistent with established mechanisms for the biosynthesis of a particular class of glycans. To this end, we have implemented Qrator, a web-based application that uses a combination of external literature and database references, user annotations and canonical trees to assist and guide researchers in making informed decisions while curating glycans. Using this application, we have started the curation of large numbers of N-glycans, O-glycans and glycosphingolipids. Our curation workflow allows creating and extending canonical trees for these classes of glycans, which have subsequently been used to improve the curation workflow.